Small intestinal bacterial overgrowth syndrome in children - Siniewicz-Luzeńczyk, Katarzyna; Bik-Gawin, Agnieszka; Zeman, Krzysztof; Bąk-Romaniszyn, Leokadia (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction: Small intestinal bacterial overgrowth syndrome (SIBO) is defined as an increased number of nonpathogenic bacteria over 10 5 organisms in 1 millilitre of small intestine content. The most common predisposing factors include, among others, gut motility disorders and chronic use of proton pump inhibitors. The results of recent studies indicate the importance of SIBO in gastrointestinal diseases. Aim: To assess the prevalence of SIBO in children with abdominal pain. Material and methods: One hundred children (59 girls and 41 boys) aged from 4 to 17 years (mean age: 10.47 ±3.73 years), hospitalised due to abdominal pain, were enrolled in the study. Hydrogen breath test (HBT) with lactulose was established among all patients. Expired air was analysed using a Gastrolyzer (Bedfont). Results: The HBT result was positive in 63 (63%) children with abdominal pain; including 40 girls (67.8%) and 23 boys (56.1%). The test was positive in the group of 29 (46%) children aged under 10 years and in the group of 34 (54%) children aged over 10 years. Among the patients who reported for the control study 88% achieved a normalisation of HBT after treatment. Conclusions : The prevalence of positive HBT results in the group of patients with abdominal pain is over 60%. Small intestinal bacterial overgrowth syndrome should be considered as one of the causes of abdominal pain in children. The SIBO in children shows a good response to treatment.